Direct Acoustic Cochlear Implants Lead to an Improved Speech Perception Gap Compared to Conventional Hearing Aid. Issue 9 (October 2018) - Maier, Hannes; Lenarz, Thomas; Dolležal, Lena-Vanessa; Busch, Susan
Abstract : Objectives: The objectives of this study was to evaluate the aided speech perception in quiet of direct acoustic cochlear implant (DACI) patients and the speech perception gap in comparison with hearing aid users. Study Design: Retrospective comparative study. Setting: Tertiary referral center. Patients: Adults with moderate-to-severe mixed hearing loss who have been implanted with a DACI and fitted with a processor for at least 6 months. Intervention(s): Comparison of aided monosyllabic word scores and speech perception gap of 59 DACI-implanted ears speech perception gap with published data on 208 ears aided with a conventional hearing aid (HA) divided into four different hearing loss groups between 35 and 75 dB HL. Main Outcome Measure(s): Aided monosyllabic word score, predicted maximum monosyllabic word recognition score (PBmax ) and speech perception gap. Results: In terms of aided speech perception, DACI patients with cochlear reserves between 45 and 65 dB HL have a significant advantage compared with conventional HA users. A speech perception gap of 11% points for DACI and 21% points for conventional HAs were determined and an approximation of PBmax is achieved by 52% of the DACI patients compared with only 36% of the HA users. Conclusions: For patients with moderate-to-severe inner ear hearing loss between 45 and 65 dB HL, better speech perception in quiet is obtained with the DACI system. Compared with conventional hearing aids, speech performance with the DACI is closer to the maximally possibly score PBmax .